Modification of textile wastewater treatment system by gamma-irradiation - Jo, Hun-Je; Lee, Sun-Mi; Kim, Hyo-Jin; Park, Eun-Joo; Kim, Jeoung-Gye; Chung, Hung-Ho; Jung, Jinho (ELSEVIER SCIENCE INC, 2006)
To modify a textile wastewater treatment process, the effects of gamma-ray treatment on the biodegradability and toxicity of wastewaters from each unit process of a textile wastewater treatment plant (WWTP) were investigated in this study. Gamma-irradiation did not improve the biodegradability of the raw wastewater (RW) and wastewater after coagulation and flocculation (WCF), but it increased the biodegradability of the final effluent (FE) from 0.008 to 0.17 at a dose of 20 kGy. In addition, gamma-rays significantly improved the biodegradability of weight-loss wastewater (WLW) from 0.72 to 0.91 at a specific dose of 1 kGy. An acute toxicity test, using Daphnia magna, showed that the toxicity change induced by gamma-rays was dependent on the chemical property of the wastewater. Thus, gamma-irradiation decreased the toxicity of RW while increasing the toxicity of WCF. For FE and WLW samples, no toxicity change was observed after radiation treatment. From this study, it appears that radiation treatment of WLW following biological treatment is most desirable.
Keywords: BIODEGRADABILITY; IMPROVEMENT; EFFLUENT; TOXICITY; SEWAGE; SLUDGE; DYES